Sistem Informasi Menajemen Aset (Studi Kasus: Desa Barepan) - Setyawan, Haris; Asroni, Asroni (Semesta Teknika, 2018)
Barepan Village is one of the villages in Cawas sub-district, Klaten, Central Java. In 2017 Barepan Village has owned a new building as a means of village administration and obtains assets that support the implementation of government such as computers, tables, chairs, and others. However, asset management is currently not going well and does not have a unique asset database to facilitate the management and tracking of its assets. This caused the difficulty of conducting asset track which made it difficult for asset managers to know the condition of the asset was right, damaged or lost. Therefore, an information system is needed which has the objective to be able to run the business process of asset management to be neat and structured so that asset managers can efficiently manage and track assets. The process of designing an Asset Management Information System using the waterfall model software development method begins with needs analysis, design, coding, testing, and maintenance. From the design stage, it was then created with Code Igniter in the form of a PHP framework with the MVC concept so that a website-based Information System with the MVC concept was produced. Verification and validation are then carried out to determine the suitability of the system design with the Asset Management Information System final results that have been made. Finally, an asset information system can be obtained that fits your needs and archives assets well.